Alternative Feeds for Beef Cattle - Robert O. Myer; Mary B. Hall (EDIS)
Cattle producers frequently seek low-cost feed alternatives, especially when traditional feeds are expensive. Many of these “alternative” feeds are by-products (or co-products) and waste products from the processing of various food and fiber crops, or crop residues. These alternative feeds can fit into a feeding program as the primary roughage, as a supplement to a regular ration, or as a replacement for part of the ration. This document is AN128, one of a series of the Animal Science Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date September 19, 2003.